2018
DOI: 10.4314/jasem.v22i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of bioethanol production from simultaneous saccharification and fermentation of pineapple peels using <i>Saccharomyces cerevisiae</i>

Abstract: ABSTRACT:In this study, bioethanol production from the simultaneous saccharification and fermentation (SSF) of pineapple peels using cellulase and Saccharomyces cerevisiae was investigated. A three-factor Box-behnken design (BBD) and response surface methodology (RSM) were employed to study the effect of broth pH (2-6), yeast loading (2-10 g/l) and ammonium sulphate concentration (1-5 g/l) on the bioethanol production process. Optimum values of pH, yeast loading and ammonium sulphate concentration of 6.0, 8ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…At p value ≤ 0.05, there was no statistically significant difference between the pH values of the yeasts during fermentation. The fluctuation in the pH do not affect yeast growth, but instead promotes yeast growth and ethanol formation while also acting as a deterrent to bacterial contaminants and favoring more catabolic reactions [44,45]. The increase in dry yeast cell mass indicated rapid cell growth (Fig.…”
Section: Ph Of Sample During Fermentationmentioning
confidence: 98%
“…At p value ≤ 0.05, there was no statistically significant difference between the pH values of the yeasts during fermentation. The fluctuation in the pH do not affect yeast growth, but instead promotes yeast growth and ethanol formation while also acting as a deterrent to bacterial contaminants and favoring more catabolic reactions [44,45]. The increase in dry yeast cell mass indicated rapid cell growth (Fig.…”
Section: Ph Of Sample During Fermentationmentioning
confidence: 98%
“…Hayder et al [10] also reported the optimum conditions for bioethanol produced from lignocellulosic biodegradable municipal solid wastes (BMSW) using RSM as; an initial substrate concentration of 75g/L, pH of 6.0, fermentation time 39hours and a yeast concentration of 2ml/L. Similarly, Oiwoh et al [11] reported the highest ethanol concentration of 5.82%v/v produced under the optimum conditions of pH 6.0, ammonium sulphate concentration of 5g/L and a yeast oncentration of 8% (v/v). Bioethanol production from cheese whey using sacccharomyces cerevisiae DIV13ZZ087COVS strain was also optimized using CCD and the optimum conditions for fermentation temperature, pH and yeast extract concentration were found to be 28.38ᵒC, 4.31 and 3.969 g/L respectively under which an ethanol concentration of 18.53g/L after 24hours incubation time was produced [12].…”
Section: Nwogwugwu Et Almentioning
confidence: 99%
“…However, increase in bioethanol production using first-generation biofuels has raised concerns about food security and fertile land. Thus, the exploration for second-generation biomass has mostly concentrated on cheap and abundant lignocellulosic municipal waste [4][5][6].…”
Section: Introductionmentioning
confidence: 99%